A divisão sexual do trabalho como fenômeno social: uma crítica feminista ao trabalho doméstico - Barbara Almeida Duarte (2018)
The present research exposes the way in which the sexual division of labor was incorporated by the capitalist production system, allowing the gender to remain an important tool of marginalization. In this way, the philosophical thought of Marxist strand was sought the basis for a critique of the way in which women are inserted in society. We start from the view that work, in a broad sense, refers to the transformations that the human being performs in nature, in himself, and in his relations with others in society. In confirming that the female insertion in society is established in a limiting way to the development of human potential, notably under the influence of capitalism, it is sought to find out how this is reflected in the world of work. That is, in the work understood as a relation in which the capitalist system of production is concretized, based on the separation between worker and means of production and the exploitation of one human being on the other, it is necessary to problematize the occurrence of gender splits of the most varied forms as they occur, all of them corroborating the idea that, in fact, the gender factor presents itself as a divisor of social relations next to the class. Thereafter, domestic work was chosen to demonstrate the occurrence and maintenance of women's domination-exploitation under capitalism, and in the end, to understand how law reflects these distinctions.